2014
DOI: 10.1186/1475-2891-13-79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine supplementation on oxidative stress and antioxidant enzymes activities in patients with coronary artery disease: a randomized, placebo-controlled trial

Abstract: BackgroundCardiovascular disease is the leading cause of death worldwide. Higher oxidative stress may contribute to the pathogenesis of coronary artery disease (CAD). The purpose of this study was to investigate the effect of L-carnitine (LC, 1000 mg/d) on the markers of oxidative stress and antioxidant enzymes activities in CAD patients.MethodsWe enrolled 47 CAD patients in the study. The CAD patients were identified by cardiac catheterization as having at least 50% stenosis of one major coronary artery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 29 publications
(33 reference statements)
4
74
1
4
Order By: Relevance
“…L-carnitine is a dietary supplement with known antioxidant properties and has been reported to have beneficial effects in common chronic diseases. Previous studies have shown that L-carnitine supplementation decreases MDA concentrations significantly in healthy women [41], type 2 diabetic [19], coronary artery disease [20] and hemodialysis patients [21,22]. Lee et al [20] reported that Lcarnitine supplementation increased levels of antioxidant enzymes activities [e.g., catalase…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…L-carnitine is a dietary supplement with known antioxidant properties and has been reported to have beneficial effects in common chronic diseases. Previous studies have shown that L-carnitine supplementation decreases MDA concentrations significantly in healthy women [41], type 2 diabetic [19], coronary artery disease [20] and hemodialysis patients [21,22]. Lee et al [20] reported that Lcarnitine supplementation increased levels of antioxidant enzymes activities [e.g., catalase…”
Section: Discussionmentioning
confidence: 98%
“…L-carnitine is a dietary supplement that plays an important role in shuttling the long-chain fatty acids across the inner mitochondrial membrane for β-oxidation and ATP production [17] and prevents the accumulation of end-products of lipid peroxidation due to its antioxidant effects [18]. According to previous studies, levels of malondialdehyde (MDA) decreased significantly after L-carnitine supplementation in type 2 diabetic [19], coronary artery disease [20] and hemodialysis patients [21,22]. Furthermore, Malaguarnera et al reported that L-carnitine supplementation in type 2 diabetics [19] and in NASH patients [23] led to significant decrease in serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) levels.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Finally, LC antioxidant power may be due to its ability to increase activities of antioxidant enzymes like SOD and others 7,8,25 . Regarding ML, it was reported to correct lipopolysaccharide (LPS)-induced elevations in TBARS and depletion in GSH in a lung model of injury 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It participates in the metabolism of branched chain amino acids, beta oxidation of fatty acids, and cell membrane stabilization. LC was reported by many in vitro and animal studies to have free radical scavenging potential scavenger, thus protecting antioxidant enzymes from oxidative damage 7 . It also has proved to possess anti-inflammatory activity 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Carnitine metabolic impairments have also been observed in CFS (Kuratsune et al, 1994), and some clinicians prescribe l-carnitine dietary supplements as therapies for their patients (Huang et al, 2013;Lee et al, 2014;Cruciani et al, 2015). Symptoms such as exercise intolerance manifesting as acute crises of early fatigue and contractures, sometimes in combination with rhabdomyolysis and recurrent myoglobinuria, are also associated with McArdle disease (myophosphorylase deficiency, OMIM 232600) (McArdle, 1951), a disorder caused by homozygous or compound heterozygous mutations in the PYGM gene.…”
Section: Introductionmentioning
confidence: 99%